2013
DOI: 10.1016/j.jpha.2013.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Voltammetric quantitation of nitazoxanide by glassy carbon electrode

Abstract: The present study reports voltammetric reduction of nitazoxanide in Britton–Robinson (B–R) buffer by cyclic and square-wave voltammetry at glassy carbon electrode. A versatile fully validated voltammetric method for quantitative determination of nitazoxanide in pharmaceutical formulation has been proposed. A squrewave peak current was linear over the nitazoxanide concentration in the range of 20–140 µg/mL. The limit of detection (LOD) and limit of quantification (LOQ) was calculated to be 5.23 μg/mL and 17.45 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Table III compares the detection limit of the proposed method with the other reported methods. 28,30 As summarized in …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table III compares the detection limit of the proposed method with the other reported methods. 28,30 As summarized in …”
Section: Resultsmentioning
confidence: 99%
“…25 The review of literature revealed that few methods have been reported for the determination of nitazoxanide in pharmaceutical formulations viz., spectrophotometric, 26 liquid chromatography, 27 reverse phase high performance chromatography (RP-HPLC), 28 spectrophotometric with high performance chromatography 29 and voltammetric. 30,31 Modern electroanalytical techniques are becoming increasingly important for the determination of pharmaceutically z E-mail: rajeevjain54@yahoo.co.in significant compounds. [32][33][34][35] Electroanalytical techniques are time saving, cost effective, provide qualitative and quantitative information.…”
mentioning
confidence: 99%
“…The accuracy of an analytical method expresses the closeness of agreement between the value which is accepted either as a conventional true value or an accepted reference value and the found value [55][56][57][58]. The accuracy of the tested methods was estimated taking into consideration the percentage relative error (Err) calculated according to the following equation:…”
Section: Accuracymentioning
confidence: 99%
“…The drug must be monitored for quality assurance in preparations and to achieve the best therapeutic doses while limiting the risk of toxicity [3]. There are few analytical literature reviews for estimation of NTZ such as spectrophotometry [4][5][6], HPLC [7][8][9], HPTLC [4,10,11], and stripping voltammetry [12][13][14][15]. Also, some bioanalytical methods for quantitation of NTZ were reported [16][17][18].…”
Section: Introductionmentioning
confidence: 99%